Pengaruh Jenis Sumber Nitrogen terhadap Karakteristik Nata De Sago - Heni Mutmainnah; Farida Renhoat (Bionature, 2022)
Nata is a biotechnology product that using Acetobacter xylinum in synthesizing cellulose through a fermentation process. The raw materials for making nata generally use coconut water, fruit extracts, or tofu processing waste as a source of carbohydrates. However, in this study, sago leachate was used because it contains starch as a carbon source to form polysaccharides. Nitrogen sources are also needed in stimulating the growth of A. xylinum. The nitrogen sources commonly used are urea, ZA, and mung bean sprout extract. This study aims to determine the effect of giving different types of nitrogen sources, namely urea, ZA, and touge extract on the characteristics of nata de sago. This study used RAL (Completely Randomized Design) which consisted of 3 treatments and 3 repetitions. The results showed that the variety of nitrogen sources had a significant effect on the thickness, texture, and aroma of nata de sago, but did not significantly affect the color characteristics of nata de sago.